Effect of vinylene carbonate additive in polyacrylate-based polymer electrolytes for high-voltage lithium-metal batteries - Lulu Ren; Peichao Zou; Lei Wang; Yaqi Jing; Huolin L. Xin (Energy Materials and Devices)
Solid polymer electrolytes (SPEs) have attracted considerable attention for solid-state lithium-metal batteries (LMBs) with high energy density and enhanced safety for future applications. In this study, an SPE was developed based on a poly(ethyl acrylate) (PEA) polymer matrix with the vinylene carbonate (VC) additive (defined as PEA-VC) for high-voltage solid-state LMBs. Results show that introducing the VC additive into the PEA-based SPE leads to high lithium-ion conductivity (1.57 mS/cm at 22°C), a high lithium-ion transference number (0.73), and a wide electrochemical stability window (up to 4.9 V vs. Li/Li+). The remarkable compatibility of the PEA-VC SPE with lithium metal anodes and high-voltage cathodes was demonstrated in Li//Li symmetric cells (800 h lifetime at a current density of 0.1 mA/cm2 at 22°C) and Li//LiNi0.8Mn0.1Co0.1O2 (NMC811) full cells (with a capacity retention of 77.8% after 100 cycles at 0.2C). The improved stability is attributed to the introduction of the VC additive, which helps form a robust cathode–electrolyte interphase, effectively suppressing parasitic interface side reactions. Overall, this study highlights the role of VC additives in high-voltage and solid-state LMBs, offering a general yet effective approach for addressing the interfacial instability issue through an additive-engineering strategy.